Jessica Krug , Fugitive Modernities: Kisama and the Politics of Freedom (Durham: Duke University Press, 2018), 280 pp, paperback, ISBN 9781478001546 - Ahmad, Mahvish (Kronos: Southern African Histories, 2019)
I am no scholar of Angola. I am not particularly knowledgeable about Portuguese colonialism; I have learnt the trans-Atlantic slave trade, yes, but no more than other informed readers disturbed by its ongoing afterlives. It is therefore telling that I came across Jessica Krug’s Fugitive Modernities in a conversation with friends similarly unacquainted with West Central Africa and the Americas, but, like me, animated by questions that lie at the heart of this book: How do we write about the disappeared? How to put into words communities whose worlds have been targeted in acts of mass violence? How do we narrate the worlds of those who actively tried to evade the power that, as Trouillot reminds us, makes and records history? My friends and I focus on post-20th century communities elsewhere upended by other forms of violence, including settler-colonial destruction in Palestine, the Ottoman genocide of Armenians, and imperial war in the Afghanistan-Pakistan border regions.1 In contrast, Fugitive Modernities engages the ideas of communities escaping the grip of brutal states and the violence of the trans-Atlantic slave trade around present-day Angola, Colombia and Brazil from the 16th century until today. That Krug’s work reverberates across time and space is a testament not only to its intellectual, political and methodological innovations; it is also an important reminder that breaking down the imperially imposed boundaries represented in area studies is a crucial step on our path to decolonisation. Places, peoples and ideas out of Angola can help us rethink the world...